POLA MAKAN DAN AKTIVITAS FISIK DENGAN KEJADIAN HIPERTENSI DI PUSKESMAS PERAWATAN HITU - Wahyuni (Fakultas Kesehatan Masyarakat Universitas Dayanu Ikhsanuddin, 2023)
Hypertension is a condition when the blood pressure against the artery walls is too high. Increased sodium intake causes the body to retain fluid, which increases blood volume. High-fat intake can increase fat levels in the blood and result in plaque formation. Physical activity is known to reduce the risk of hypertension. This study aimed to determine the description between eating patterns and physical activity with the incidence of hypertension at the Hitu Care Community Health Center. The type of research is quantitative research with a descriptive approach. The instruments in this research were a 3x24-hour food recall questionnaire, IPAQ, and sphygmomanometer measurements. Of the 18 responden, 11 people had grade I, and 7 people had grade II. 9 people fell into the recommended sodium intake category and 2 people fell into the not recommended category, while of the 7 people who had hypertension II, 5 people fell into the recommended sodium intake category, and 2 people fell into the recommended sodium intake category, and 2 people fell into the recommended sodium intake category. 10 people had the recommended fat intake and 8 people had the recommended fat intake. 11 people had light physical activity, 6 people had moderate physical activity, and 1 person had heavy physical activity. The research results show that hypertension mostly come from consuming snacks such as bread, and instant milk, and also some people have the habit of consuming fatty foods because food processing is often by frying and using coconut milk repeatedly.